2015
DOI: 10.1371/journal.pone.0117352
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Lymphatic Endothelial Progenitors in Lymphatic Malformation Development

Abstract: Lymphatic malformations (LMs) are vascular anomalies thought to arise from dysregulated lymphangiogenesis. These lesions impose a significant burden of disease on affected individuals. LM pathobiology is poorly understood, hindering the development of effective treatments. In the present studies, immunostaining of LM tissues revealed that endothelial cells lining aberrant lymphatic vessels and cells in the surrounding stroma expressed the stem cell marker, CD133, and the lymphatic endothelial protein, podoplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…However, it remains unclear as to whether LECs are involved with the regulation and mechanistic functions of bFGF in chondrosarcoma. Growing evidence indicates that LECs are associated with abnormal lymphangiogenesis via the induction and modulation of VEGF-C [39, 40]. In the present study, we found that CM from bFGF-treated chondrosarcoma cells increased LEC migration and tube formation, implying that bFGF enhances lymphangiogenesis in chondrosarcoma cells.…”
Section: Discussionsupporting
confidence: 70%
“…However, it remains unclear as to whether LECs are involved with the regulation and mechanistic functions of bFGF in chondrosarcoma. Growing evidence indicates that LECs are associated with abnormal lymphangiogenesis via the induction and modulation of VEGF-C [39, 40]. In the present study, we found that CM from bFGF-treated chondrosarcoma cells increased LEC migration and tube formation, implying that bFGF enhances lymphangiogenesis in chondrosarcoma cells.…”
Section: Discussionsupporting
confidence: 70%
“…Although PDGFRβ and NG2 are considered mural cell markers in the vasculature (21,22), both are expressed in progenitor cells. NG2 expression has been reported in bone marrow mesenchymal stem cells (29,30), neuronal progenitor cells (31,32), and lymphatic malformation progenitor cells (33). Similarly, PDGFRβ is expressed in circulating endothelial progenitors, as well as hemangioblasts (34,35), suggesting that HemECs have failed to terminally differentiate from endothelial progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other models involving gene deletions or implantation of cells from human lymphatic malformations have been used to mimic human lymphatic disorders (37)(38)(39)(40). These models have proven useful in characterizing these conditions but are yet to be used to study the regression of abnormal lymphatics.…”
Section: Attributes and Limitations Of The Ccsp/vegf-c Mouse Model Ofmentioning
confidence: 99%